ANALISIS PENYUSUNAN ANGGARAN UNIT PEMELIHARAAN JALAN DAN JEMBATAN WILAYAH IV TAHUN ANGGARAN 2012 DINAS PEKERJAAN UMUM PROVINSI KALIMANTAN BARAT - B51110095, DIAN IRAWATI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
One of the important problems in the management of the Government's financial budget. Authors, the budget should be transparency in the form of receipts and expenditures and budgets can be put to their best in order to achIn connection with the explanation above, then in the study and discussion of the study of the process of drafting the budget unit maintenance of roads and bridges, by lifting the title "compilation of Budget Analysis Unit Maintenance of roads and bridges, the region IV fiscal year 2011 Public Works Agency province of West Kalimantanieve organizational goals that prosper society. In this study, the author uses descriptive qualitative approach method of describing the State of the object of research based on the available data. With the method of data collection in the form of direct communication techniques (interviews), data collection using the questionnaire and the study of librarianship. Data analysis technique used is to analyze problems using opinion by depicting all the existing data and information from the research literature with books. From the authors of the research results obtained regarding the preparation of the budget unit, road maintenance and bridge the region IV fiscal year 2011 public works of west kalimantan province which includes the preparation of RKPD, the submission and draft PPAS KUA by chairman TAPD to local governments to the DPRD, the submission by PPAS and KUA area to the DPRD, KUA and PPAS agreed between regional and provincial heads, circular letter head of the subject guidelines RKA-SKPD, Preparation and discussion of RKA RKA-SKPD-and PPKD as well as the preparation of the draft budget, the submission of a draft budget to parliament, making mutual agreement of PARLIAMENT and the head of the region, the results of evaluation of draft budgets and the determination of the budget in accordance with the results of Perda evaluation. Constraints encountered in the preparation of budgets and road maintenance Unit in the bridge Region IV Public Works Agency province of West Kalimantan is divided into two parts which constraint is internal and external constraints. Keywords : budget, budget and Revenue shopping districts, public sector, financial Area